Climate change impacts and adaptation strategies for crops in west Africa: a systematic review - Carr, T.W.; Mkuhlani, S.; Segnon, A.C.; Ali, Z.; Zougmoré, Robert B.; Dangour, Alan D.; Green, R.; Scheelbeek, P. (IOP Publishing, 2022)
Agriculture in West Africa faces the challenge of meeting the rising demand for food as national incomes and populations increase while production becomes more uncertain due to climate change. Crop production models can provide helpful information on agricultural yields under a range of climate change scenarios and on the impact of adaptation strategies. Here, we report a systematic review of the impact of climate change on the yield of major staple crops in West Africa. Unlike earlier reviews we pay particular attention to the potential of common agricultural adaptation strategies (such as optimised planting dates, use of fertilisers and climate-resilient crop varieties) to mitigate the effects of climate change on crop yields. We systematically searched two databases for literature published between 2005 and 2020 and identified 35 relevant studies. We analysed yield changes of major staple crops (maize, sorghum, rice, millet, yam, cassava and groundnuts) caused by different climate change and field management scenarios. Yields declined by a median of 6% (−8% to +2% depending on the crop) due to climate change in all scenarios analysed. We show that the common adaptation strategies could increase crop yields affected by climate change by 13% (−4% to +19% depending on the strategy) as compared to business-as-usual field management practices, and that optimised planting dates and cultivars with longer crop cycle duration could in fact offset the negative effects of climate change on crop yields. Increased fertiliser use has not mitigated the impact of climate change on crops but could substantially increase yields now and in the future. Our results suggest that a combination of increased fertiliser use and adopting cropping practices that take advantage of favourable climate conditions have great potential to protect and enhance future crop production in West Africa.